2007
DOI: 10.1038/sj.onc.1210792
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling related to poor prognosis in thyroid carcinoma. Combining gene expression data and biological information

Abstract: Undifferentiated and poorly differentiated thyroid tumors are responsible for more than half of thyroid cancer patient deaths in spite of their low incidence. Conventional treatments do not obtain substantial benefits, and the lack of alternative approaches limits patient survival. Additionally, the absence of prognostic markers for well-differentiated tumors complicates patient-specific treatments and favors the progression of recurrent forms. In order to recognize the molecular basis involved in tumor dediff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 42 publications
2
61
0
1
Order By: Relevance
“…46 However, approximately 2% to 5% of MEN2 families do not have RET mutations, and many cases of sporadic MTC do not carry RET mutations. 47,48 The absence of RET mutations suggests the existence of additional loci predisposing to MEN2 and sporadic MTC. Other genes, including those encoding components of the retinoblastoma (RB) and P53 tumorsuppressor pathways and RAS proto-oncogene may be involved in MTC formation.…”
Section: Cancermentioning
confidence: 99%
“…46 However, approximately 2% to 5% of MEN2 families do not have RET mutations, and many cases of sporadic MTC do not carry RET mutations. 47,48 The absence of RET mutations suggests the existence of additional loci predisposing to MEN2 and sporadic MTC. Other genes, including those encoding components of the retinoblastoma (RB) and P53 tumorsuppressor pathways and RAS proto-oncogene may be involved in MTC formation.…”
Section: Cancermentioning
confidence: 99%
“…The over-expression of PKB in poorly differentiated thyroid carcinomas was first demonstrated by Rodrigues et al (2007b), who emphasized the importance of the MAP kinase pathway in the progression of thyroid carcinomas. Montero-Conde et al (2008) investigated differentiated and undifferentiated thyroid tumors by using cDNA microarrays and also reported significant changes in the expression of genes of the MAPK pathway, as well as those of the TGFb pathway, focal adhesion, and activation of actin polymerization and cell cycle. Ito et al (2009) reported the co-expression of S100A8 and A100A9, which represent the S100 calcium-binding proteins A8 and A9, in undifferentiated thyroid carcinomas, and the lack of S100A8 expression and a weak expression of S100A9 in PDTC, and lack of these proteins in well-differentiated DTC.…”
Section: Transcriptome Of Pdtc and Undifferentiated Thyroid Cancer Inmentioning
confidence: 99%
“…10 Taking advantage of the available data from mRNA and miRNA expression from the same tumors, MirRGate, a specific tool for miRNA targets' identification, was used for target prediction (http://mirgate.bioinfo.cnio.es/API/). The miRNA was considered regulatory if its expression was negatively correlated with that of the target mRNA as assessed by Pearson's correlation test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Similarly to other genomic features, [8][9][10] the miRNA expression fingerprints have been shown to be subtype-and driver alteration-specific (reviewed in Pallante et al 11 ). Moreover, the role of polymorphisms in the complementary sites of target mRNAs was initially proposed in the context of papillary carcinomas, 12 and polymorphisms in the miRNA sequence itself were shown to be predisposing to thyroid cancer, 13 highlighting the role of miRNAs in thyroid tumorigenesis.…”
mentioning
confidence: 99%